Avaliação de investimentos pelo método de equivalência patrimonial: um estudo comparativo da aplicação das normas brasileiras, norte-americanas e internacionais - Delfino, Angelita (Universidade do Vale do Rio do Sinos, 2008)
This study aims at describing the similarities and the differences observed in the measuring and accounting treatment process of the investments valued by the equity method, through the application of the Brazilian rules (CVM), international rules (IASB) and north-American rules (FASB). For this purpose, a theoretical referential was developed, examining the following: a) accounting information; b) corporative governance; c) rule creators; d) accounting harmonization; e) criteria for evaluating investments, this one includes details of the equity method. The research developed is applied; classified according to the objectives as descriptive, and for the technical procedures the comparative method was used. The main results from the analysis of the data (fictitious situations) showed that: from the eight topics analyzed, three have the same treatment in the three different standards; three have differences when evaluating or registering; and two topics differ in part, however they have similarities.
Keywords: harmonização; normas brasileiras; normas internacionais; normas norte-americanas; equivalência patrimonial; harmonization; international rules; equity method; Ciências Sociais Aplicadas